A literary view to the road chronotope in modern American poetry - Yunusova Ganjina Rustamovna (Periodica Journal, 2024)
The following article takes a deep dive into the chronotope phenomenon, specifically the road chronotope, and analyses poetic features of it through exploring modern American poetry. Variety of versions and metaphorical aspects of the road chronotope have been observed with the help of the poem “The Road not taken” by Robert Forest. The poet, as a human being, sees and understands the world in three dimensions as well as the writer does. Consequently, the concern of the road chronotope becomes one of the pivotal issues in poetry that we try to shed the light through literary analyses
Keywords: chronotope of the road; The Road Not Taken